Downsizing the labor force by low and high profit firms: an experimental analysis - Werner Güth; Christian Paul (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
One may hope to capture the behavioral and emotional effects of downsizing the laborforce in rather abstract settings as an ultimatum game (see Fischer et al. (2008)), or try to explore downsizing in its more natural principalagent scenario with a labor market background. We pursue the latter approach and test experimentally wether downsizing occurs whenever (game) theoretically predicted and whether effort reactions qquestion its profitability. Our main findings are that downsizing seems to happen less often than predicted and that its frequency does not depend on whether, theoretically, its gains are rather large or small. Interestingly, we also find strong evidence that piece-rate offers are used in a suboptimal way.
Keywords: C72; C91; D21; J01; 330; Downsizing; experimental economics; principal-agent model; labor; economics; Personalabbau; Arbeitsproduktivität; Arbeitsbeziehungen; Agency Theory; Nichtkooperatives Spiel; Test